The Role Of Career Path Management In Achieving Organizational Loyalty Among Syrian Arab Red Crescent Volunteers _ Lattakia Branch - محلا براءة; قاسم سامر; سليطين سوما (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to study the role of the dimensions of career management (training, promotion, motivation, job rotation) in achieving organizational loyalty. The researcher adopted the descriptive analytical approach, Where the data were collected by the methods of questionnaire and personal interview, and the research sample was 154 volunteers in the Syrian Arab Red Crescent.. Among the most important findings of the study is the existence of a moral relationship between career management and organizational loyalty among Syrian Arab Red Crescent volunteers, as the individual consciously and rationally chooses the organization that seeks to satisfy his human desires and needs, and recognizes his competence and ability to achieve an added value to it. It gives him an opportunity to highlight his skills in different jobs, and acquire new skills. Therefore, feeding these requirements facilitates the formation of trust between the individual and his organization. Keywords: career path management, organizational loyalty, training, promotion, motivation, job rotation.